Healthcare cost containment. - Goh, Mui Kiang. (2013)
This report attempts to give an overview of the state ofhealthcare cost and the various cost containment methods employed by various countries. The rising cost of healthcare provision throughout the world have provoked a vigorous debate about the design of healthcare systems and the role of government in healthcare.